Design of a Microcontroller-based Hydrostatic Pressure Experiment Tool in Science Education - Angjelina, Putri; Prima, Eka Cahya; Riandi, Riandi; Anwar, Sjaeful (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2023)
This study aims to create a microcontroller-based hydrostatic pressure experiment tool in science education. The digital system makes the tools used more effective and time-efficient. The digital system used in this tool consists of a microcontroller, digital display (LCD), and the MS5637 Barometer sensor. This series of tools processes digital data into hydrostatic pressure, displayed on the LCD. The method used in this study is following Archimedes' principle. The independent variable in this study is the depth of the funnel thrust into the measuring cup, while the dependent variable is the hydrostatic pressure displayed on the LCD. The results showed that the hydrostatic pressure valuesobtained were close to theoretical calculations. Then, the r-squared result between Δh of water and hydrostatic pressure through experiments with a microcontroller (Arduino) is 0.9981. This value is good enough to show the proportion or percentage of hydrostatic pressure affected by Δh of water. Thus, experiments using this tool are quite effective in science learning.